A multiresolution method for simulating infinite periodic arrays. - Filipovic, D.S (IEEE Transactions on antennas and propagation)
Hierarchical mixed-order tangential vector finite elements (TVFEs) for tetrahedra are attractive for accurate and efficient analysis of a wide class of electromagnetic radiation and scattering problems. They provide versatile geometrical modeling and accurate field representation by allowing combination of lowest and higher order TVFEs. In this letter, the finite-element boundary-integral (FE-BI) method with hierarchical TVFEs for tetrahedra is used for analysis of infinite, doubly periodic antenna arrays. It is shown that accurate prediction of array scanning properties can be obtained by using higher order TVFEs in the regions where large fields and rapid field variations are expected and lowest order TVFEs elsewhere. This is demonstrated in the case of a microstrip patch array